2000
DOI: 10.1111/j.1442-9993.2000.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Fire regimes of World Heritage Kakadu National Park., Australia

Abstract: LANDSAT Multi-Spectral Scanner imagery was used to determine aspects of the fire regimes of Kakadu National Park (in the wet-dry tropics of Australia) for the period 1980-1995. Three landscape types recognized in this Park were Plateau, Lowlands and Floodplain. Areas burned in early and late dry seasons each year were documented using a Geographical Information System. Regression analyses were used to examine time trends in the areas burned each year and the interrelationships between early and late dry season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 13 publications
0
54
0
Order By: Relevance
“…During the period 1980-1995, 50-60% of lowland savanna was burned each year, and 70% burned at least once every 2 years (Gill et al, 2000). Interestingly, there was a near 1:1 trade-off between burning in the early and in the late dry season, and an apparent shift to more, early season burning in the latter part of that period.…”
Section: Discussionmentioning
confidence: 97%
“…During the period 1980-1995, 50-60% of lowland savanna was burned each year, and 70% burned at least once every 2 years (Gill et al, 2000). Interestingly, there was a near 1:1 trade-off between burning in the early and in the late dry season, and an apparent shift to more, early season burning in the latter part of that period.…”
Section: Discussionmentioning
confidence: 97%
“…98 -100, 127 -128); surprisingly, few systematic studies of the significance of seasonality for landscape in the Nordic countries have been carried out since (Jones, 2004). Elsewhere, there have been some studies on how people perceive the changes in landscape (see, for example, Higuchi, 1983;Porteous, 1990), and there have been studies of seasonal land cover using geographical information systems (GIS) and remote sensing techniques in different parts of the world (see, for example, Ferreira et al (2003) on Brazil; Gill et al (2000) on Australia; Loveland et al (1995) for the USA). However, four publications deserve special attention.…”
mentioning
confidence: 99%
“…As Gill et al (2000) and found by analysing Landsat data, this treatment essentially works by 1:1 replacement of Late Dry Season fire with Early Dry Season fire, though in this study, the effect is slightly lower (slope −0.64 for Human Late Dry Season fires). This means that treatment does not reduce and may actually increase the overall area burnt, though account must be taken of the higher internal unburnt patchiness of Early Dry Season fires Oliveira et al 2015).…”
Section: Discussionmentioning
confidence: 90%
“…To date, the programme has been very effective, with a mean reduction in annual Late Dry Season burning from 32% to 11% per year by increasing Early Dry Season area burnt from 8% to 21% (Russell-Smith et al 2013). However, previous studies found that Early Dry Season treatment reduces Late Dry Season area burnt by a 1 to 1 replacement that suggests that Early Dry Season treatment on its own is only responsible for half of the achieved reduction in Late Dry Season burning (Gill et al 2000;. There are three possible reasons why WALFA may have been more successful than these studies predict.…”
Section: Introductionmentioning
confidence: 85%